Introduction [in The making of a blue revolution in Bangladesh] - Rashid, Shahidur (International Food Policy Research Institute, 2019)
In the last half of the 20th century, food policy in most Asian countries meant ensuring availability of cereals, mainly rice and wheat.1 The rationale for this cereal-centric policy is well understood. Agricultural productivity was low, the world market was volatile, and the national food security depended on, apart from Mother Nature, the relationship with the donor countries, which was not smooth because of ideological differences. By the early 1960s, feeding a rapidly growing population became a daunting challenge for the region’s countries. Many experts viewed these challenges as too big to handle. “Famine 1975” (Paddock and Paddock 1967), “lifeboat ethics” (Hardin 1974), and “triage” (Ehrlich 1971) were the labels commonly applied to these countries. Thanks to Green Revolution technology and concerted policy actions, none of the dire predictions turned out to be true. By the 1980s, countries in the region ensured cereal availability and began to enjoy overall economic growth (Rashid, Cummings, and Gulati 2007).